Crossed fused renal ectopia presenting as recurrent lower abdominal pain and urinary tract infection (2013)
Background: Crossed fused renal ectopia is a relatively rare condition which may remain undiagnosed for a long time. Renal function is usually preserved. It usually involves the left kidney. It is usually associated with mal-rotation, and may be a cause of urinary tract infection, hydronephrosis and renal calculi. Material and method: We report a case of a 15- year old boy who was referred to our clinic with complaints of abdominal pain, and an ultrasound report of “absent right kidney”. Results: Urine examination indicated a partially treated infection, but the tests of kidney functions were normal. Intravenous urography confirmed crossed fused renal ectopia, and a flush aortogram showed two anomalous right renal arteries arising from the left side of aorta. Conclusion: An “absent” kidney in its normal location should prompt further investigations. Recurrent chronic lower abdominal pain and urinary tract infection in a young person may be due to congenital renal abnormality. Evaluation of persistent urinary abnormalities in a child should include screening for congenital abnormalities.